Acute limb ischemia due to abdominal compartment syndrome. Issue 1 (16th July 2013) - Maeda, Atsuo; Wakabayashi, Kohei; Suzuki, Hiroshi
<x xml:space="preserve">Abstract</x> Acute limb ischemia (ALI) is caused by embolisms or progressive atherosclerosis. We report the case of a 68‐year‐old female who presented with acute total occlusion of left iliac artery due to remarkably massive ascites from pancreatic cancer. To our knowledge, no other case reports of ALI caused by acute compartment syndrome have been published. We treated our case successfully by draining the ascites fluid without any balloon angioplasty or stent implantation. The removal of extrinsic compression may be the best treatment for cases of this type. © 2013 Wiley Periodicals, Inc.